2022
DOI: 10.1097/phh.0000000000001637
|View full text |Cite
|
Sign up to set email alerts
|

Improving Partnerships Between Public Health and Public Safety to Reduce Overdose Deaths: An Inventory From the CDC Overdose Data to Action Funding Initiative

Abstract: Rates of drug overdose deaths are high and growing. Innovative strategies, such as partnerships between public health and public safety (PH/PS) agencies, are needed to curb these trends. Support for PH/PS partnerships as an overdose prevention strategy is growing; however, little information exists on the makeup of activities within this strategy. The US Centers for Disease Control and Prevention's (CDC's) Overdose Data to Action (OD2A) cooperative agreement supports innovative and comprehensive overdose surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The large number of public health and safety agencies interacting with ODMAP data in local communities to address the opioid crisis is a strength and a promising indicator that data‐sharing initiatives in the national opioid response strategy can be successful (Blanco et al., 2022; Mital et al., 2022). According to the CDC (see Figure 2), 22 of 109 (20%) states and counties receiving funding from the Overdose to Action initiative mentioned ODMAP use as one of their strategies (Mital et al., 2022). Among those grantees, the majority ( n = 16) indicated that ODMAP use will involve both public health and public safety.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of public health and safety agencies interacting with ODMAP data in local communities to address the opioid crisis is a strength and a promising indicator that data‐sharing initiatives in the national opioid response strategy can be successful (Blanco et al., 2022; Mital et al., 2022). According to the CDC (see Figure 2), 22 of 109 (20%) states and counties receiving funding from the Overdose to Action initiative mentioned ODMAP use as one of their strategies (Mital et al., 2022). Among those grantees, the majority ( n = 16) indicated that ODMAP use will involve both public health and public safety.…”
Section: Discussionmentioning
confidence: 99%